Government and industry in Britain - Grove, J. W. ([London] : Longmans, 1962)
This book presents a systematic study and analysis of the whole range of government action in economic affairs.
Imprint covered by label: New York, Humanities Press.
"Bibliographical note": p. 495-502.
oo 20/8/18
Loans
Keywords: Industrial policy; Great Britain